A Cross-sectional Study to Assess the Incidence of Adverse Drug Reactions to the Covishield Vaccine among Healthcare Workers of a Tertiary Care Government Institute in North India - Kamal Kant TRIVEDI; Punam JAKHAR; Rajesh CHAUDHARY; Lokendra SHARMA; Alka BANSAL; Mahima MAKHIJA (Modern Medicine)
Background: Vaccines are a key strategy to stop the COVID19 pandemic. The present study was conducted to assess the incidence of Adverse Drug Reactions to the Covishield vaccine among healthcare workers. Materials and Methods: A cross-sectional, observational, questionnaire-based study was carried out on healthcare workers of R.U.H.S. College of Medical Sciences, Jaipur, Rajasthan. The study tool consisted of a digital questionnaire. Results: The present study was carried out among 316 healthcare workers who received the first dose of the Covishield vaccine. 83 (26.26%) participants complained of side effects after receiving the first dose of the Covishield vaccine. Fatigue (64), fever (52), body ache (40), swelling at the vaccination site (35), headache (25), and pain in the limb (18) were the most prevalent symptoms. Most post-vaccination symptoms were found to be mild. 67 participants showed side effects of vaccination within 24 hours while 16 showed side effects after 24 hours. Conclusion: This study reflects that one fourth of participants complained of side effects after receiving the first dose of the Covishield vaccine. These side effects are not severe and should not be an obstacle to the successful control of the Covid-19 pandemic in India.